Pan-Cancer Analysis Reveals the Signature of TMC Family of Genes as a Promising Biomarker for Prognosis and Immunotherapeutic Response - Song, Jing; Tang, Yongyao; Luo, Xiaoyong; Shi, Xinpeng; Song, Fangzhou; Ran, Longke (Frontiers in Immunology, 2021)
Transmembrane Channel-like (TMC) genes are critical in the carcinogenesis, proliferation, and cell cycle of human cancers. However, the multi-omics features of TMCs and their roles in prognosis and the immunotherapeutic response of human cancer were not explored. We discovered that TMCs 4-8 were commonly deregulated and correlated with patient survival of diverse cancers. For example, TMC5 and TMC8 were correlated with relapse and overall survival of breast cancer and skin melanoma, respectively. They were validated by multiple independent cohorts. TMCs were frequently regulated by DNA methylation and somatic alterations, such as TMC5 amplification in breast cancer (523/1062, 49.2%). Six algorithms concordantly uncovered the critical role of TMCs in the tumor microenvironment, potentially regulate immune cell toxicity and lymphocytes infiltrating. Moreover, TMCs 4-8 were correlated with tumor mutation burden and expression of PD-1/PD-L1/CTLA4 in 33 cancers. Thus, we established an immunotherapy response prediction (IRP) score based on the signature of TMCs 4-8. Patients with higher IRP scores showed higher immunotherapeutic responses in six cohorts of skin melanoma (area under curve [AUC] = 0.94 in the training cohort, AUCs range from 0.63 to 0.83 in the validation cohorts). Together, our study highlights the great potential of TMCs as biomarkers for prognosis and immunotherapeutic response, which can pave the way for further investigation of the tumor-infiltrating mechanisms and therapeutic potentials of TMCs in cancer.